Operational Approaches in New Zealand & Singaporean Hotel Food & Beverage Departments: Expanding the Customer Base Beyond In-House - Bennett, Rene David (Auckland University of Technology, 2011)
Hotel-based restaurants have long been viewed as an unprofitable segment of the hospitality market and are perceived to offer a lower quality product than independently operated outlets. This thesis looks at the possible causes of this poor performance, focusing on local diners. The decision to examine this market emerged through the author’s observation that New Zealand and Singaporean diners differed in their willingness to dine in hotels. A literature review was undertaken that examined the historical development of hotel dining in each country along with media commentary on the current performance of hotel-based restaurants. Additionally, empirical research on many key areas of food and beverage (F&B) management has been examined. While prior research on many aspects of hotel F&B management exists, the majority of this focuses on the North American and British markets. This thesis represents the first piece of academic enquiry into operational issues affecting hotels in either country. This study provides a comparative look at hotel dining in Singapore and New Zealand, exploring local perceptions and the views F&B Managers have of this market. An interpretivist mixed methodological approach was undertaken, combining an online survey of local diners and interviews with F&B mangers in each country. The outputs from each of these data collection tools provided information that identified strengths and weakness within each country. The results of this primary data also allowed for a revisitation of past research to examine their transferability to Singapore and New Zealand. It also provided the opportunity to address longstanding research outcomes and test their continued relevance. Significant differences between each country were found regarding the perceptions of hotel dining held by locals. Findings indicate that New Zealand diners perceive hotel F&B products to be expensive, offering a poor standard of service combined with outdated products, where Singaporeans were much more positive. Additionally, differences exist between how F&B Managers view the need to appeal to this market with New Zealand properties maintaining their focus on providing for in-house guests, while Singaporean operators primarily focused on appealing to the local community to drive revenue. This thesis concludes that the increased willingness of Singaporeans to patronise hotel properties, together with a focus from management to actively engage the local community, has seen F&B operations become a profitable revenue stream. However, New Zealand’s hotel F&B operations face many challenges if they hope to maximize locally generated revenues. New Zealand hotels need to re-evaluate their operational strategy as offering catch-all dining options is starting to lose its appeal even to their in-house market as travelers become more savvy and venture away from hotel properties to dine. Being the first piece of research to focus on hotel based dining in either country, many operational and strategic issues have been addressed, and using best practice identified by secondary research sources as well as from the primary data collected throughout this study, recommendations have been offered that will guide operators towards improving visitation rates and their ability to attract a larger number of diners, ultimately improving revenues.
Keywords: Hospitality; Food and Beverage; Hotel; Restaurant; New Zealand; Singapore